Crecimiento Económico De La Farmacia Popular En El Recinto - Rodriguez Guerra, Juan Leonardo (2018)
he Popular Pharmacy was created in 2012 by two owners: Nancy Fuentes Coello and Magdalena Fuentes Coello to benefit the entire population of Tres Postes Precinct belonging to the Cantón Alfredo Baquerizo Moreno (Jujan) of the Province of Guayas, with the sale of pharmaceutical products, initially renting a small store and then renting a larger room to provide better customer service, currently owning a store and a new branch.